AN ANALYSIS OF CONVERSATIONAL MAXIM VIOLATION FOUND IN "THE MONSTER HOUSE" MOVIE SCRIPT - cut merya agusmita; LENI MARLINA (English Language and Literature, 2018)
ABSTRACT  Agusmita, Cut Merya. 2018. An Analysis of Conversational Maxim found in “The Monster House” movie script. Paper. Padang. English Department. Faculty of Language and Art. UNP. Conversational maxim is a set of rule or guideline in conversation which was originally proposed by HP Grice in 1975. He categorizes the maxim into four types which consist of maxim of quantity, maxim of quality, maxim of relation and maxim of manner. These rules are indeed useful for the speakers and interlocutors to make conversation run well. In this paper, the conversation or dialogue in the movie script became the source of data, and the script of the Monster House movie was chosen. Furthermore, the aim of this paper was to find out the type of maxim which is mostly violated in the script. The data were analyzed based on theory proposed by Grice. The results of the analysis revealed that almost all the main characters in the script violated the conversational maxim. Moreover, from all the utterances uttered by the characters, it was found that there were 54 utterances which violated the conversational maxim. From the 54 violated utterances, it was found that the percentages for each type of violation were 23.1% for maxim of quantity, 44,4% for maxim of relation, 9.3% for maxim of quality, 16,7% for maxim of manner, and 7,4% for combination of maxim quantity and relation.  From these results, it can be concluded that the type of maxim that was mostly violated in the script of The Monster House movie was maxim of relation. Keywords:    Conversational maxim, Maxim violation, The Monster House movie script